2020
DOI: 10.1002/jso.26351
|View full text |Cite
|
Sign up to set email alerts
|

Robotic rectal surgery: Outcomes of the first 102 totally robotic cases handled using the single‐docking technique in a reference institution

Abstract: Background and Objective Rectal cancer is often surgically treated, but it is still associated with morbidity rates. Minimally invasive techniques are increasingly being used to reduce complications, and the use of such techniques can be found in the literature. This study aims to report our experience in a reference oncology center. Methods A retrospective cohort study was performed on a prospective database of patients who underwent robotic surgery for rectal cancer using the single‐docking technique from Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 23 publications
(24 reference statements)
0
4
0
Order By: Relevance
“…Retrospective studies conducted in Brazilian institutions have shown positive outcomes, reinforcing that robotic-assisted surgery is a reliable and effective option for managing colorectal pathological conditions, such as deep infiltrating bowel endometriosis [ 20 ] and rectal cancer [ 21 ].…”
Section: Adoption Of Robotic Colorectal Surgery In Brazilmentioning
confidence: 99%
See 1 more Smart Citation
“…Retrospective studies conducted in Brazilian institutions have shown positive outcomes, reinforcing that robotic-assisted surgery is a reliable and effective option for managing colorectal pathological conditions, such as deep infiltrating bowel endometriosis [ 20 ] and rectal cancer [ 21 ].…”
Section: Adoption Of Robotic Colorectal Surgery In Brazilmentioning
confidence: 99%
“…Intraoperative complications occurred in 4.9% of patients, and only 1.9% of cases required conversion, and the average hospital stay was three days. The median number of lymph nodes harvested was fifteen [ 21 ].…”
Section: Adoption Of Robotic Colorectal Surgery In Brazilmentioning
confidence: 99%
“…Many previous studies have demonstrated that RS for rectal cancer is a safe and feasible surgical approach in terms of intraoperative complication, conversion rate, and short-term surgical outcomes [ 19 20 21 22 23 24 25 ]. Intraoperative and perioperative outcomes after rectal cancer surgery are presented in Table 1 .…”
Section: Intraoperative and Perioperative Outcomesmentioning
confidence: 99%
“…For other intraoperative and perioperative outcomes such as estimated blood loss, length of hospital stays, and postoperative morbidity including anastomotic leakage, the results of RS were comparable to those of LS without showing notable advantages, although RS was suggested to have difficulty in bleeding control [ 22 23 24 27 ].…”
Section: Intraoperative and Perioperative Outcomesmentioning
confidence: 99%